Propranolol, atenolol, and trifluoperazine reduce the spontaneous occurrence of meiotic diploid products in Saccharomyces cerevisiae. - Sora, S (1982)
The effect of atenolol, propranolol, trifluoperazine, and caffeine on the occurrence of meiotic diploid and disomic products in Saccharomyces cerevisiae was investigated. We demonstrated that atenolol, propranolol, and trifluoperazine reduce the occurrence of meiotic diploid products and that propranolol also slightly decreases the spontaneous frequency of disomics. On the other hand, caffeine appears to be a powerful inducer of diploid meiotic products, but also shows a lesser effect on disomic induction. Since spontaneous or caffeine-induced diploids arise from a failure of the second meiotic division, it appears that the target of these drugs is at the beginning of the second meiotic division. The only common effect of trifluoperazine and propranolol, mainly investigated in mammals, was an inhibition of calmodulin activity via direct interaction. We tend, therefore, to believe that calmodulin activity must be a crucial point for the second meiotic division to begin. The increased induction of diploids, due to caffeine, may be interpreted as a consequence of an increased cyclic AMP level.